Worldwide language service infrastructure : second international workshop, WLSI 2015, Kyoto, Japan, January 22-23, 2015. Revised selected papers /: second international workshop, WLSI 2015, Kyoto, Japan, January 22-23, 2015. Revised selected papers. (2016) - Unknown
No abstract available